Elaboration of High School Student’s Metacognition Awareness on Heat and Temperature Material: Wright Map in Rasch Model - Hikmah, Fitri Nur; Sukarelawan, Moh. Irma; Nurjannah, Tri; Djumati, Jamaludin (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to elaborate on the interaction between students’ metacognitive awareness and the difficulty level of items in Heat and Temperature Metacognition Awareness Inventory (HeTMAI). This study uses a quantitative research method with the type of survey research. The respondents involved were 30 students and came from one the public high schools in eastern Indonesia. Metacognitive awareness was evaluated using the 26-item HeTMAI. Student responses are administered online, are voluntary and anonymous. The interaction between students’ metacognitive awareness and items in HeTMAI was analyzed using the Wright map based on the Rasch model. The analysis results show that the student’s average ability is 1.00 logit higher than the item difficulty level. The students’ abilities ranged from -1.34 to 5.98 logit, and the item difficulty level ranged from -0.51 to 0.70. In general, it appears that most students tend to agree more easily with the statements in HeTMAI.